Atributos físicos e microbiológicos do solo em sistema de manejo orgânico e convencional com semeadura direta - Herrmann , Daniela da Rocha (2020)
The objective of this study was to evaluate in the time, areas with organic and conventional no-tillage agricultural managements, using microbiological parameters of soil quality. The experiment was conducted in an Oxisoil, from March 2017 to March 2018. The completely randomized design consisted of a factorial 6 x 5, in which the first factor were six implantation times of the organic system (6, 4, 3, 2, 1 and 0 years), and the second factor were soil collection times (0, 90, 180, 270 and 360 days), with four replications in each treatment. The samples were collected at a depth of 0 to 0.10 m from which were quantified: the total organic carbon (TOC), microbial carbon biomass (MCB), microbial quotient (qMic) and CO2 from microbial respiration (C-CO2). The highest values found for TOC, MCB and qMic were in the area characterized by direct sowing and at 1 year of the implantation time, which also has not received soil preparation during the experiment. For C-CO2, the highest values were found at 6 and 2 years, being this an attribute that may indicate greater soil degradation. In general, the microbiological attributes used in this study demonstrated that the soil with organic and tillage management increased the degradation of organic matter, thus reducing the amounts of TOC, MCB and qMic. From this study it is observed that the soil quality is negatively affected by it’s tillage to control weed plants.